2018
DOI: 10.1038/s41598-017-17518-4
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of piwi-interacting RNA pathway genes role in idiopathic non-obstructive azoospermia

Abstract: Genes involved in piwi-interacting RNAs (piRNAs) pathway have an essential role in spermatogenesis. HIWI and TDRD proteins are critical for piRNA biogenesis and function. Therefore, Mutations and polymorphisms in HIWI and TDRD genes may play role in male infertility. The aim of the present study was to investigate the role of HIWI2 rs508485 (T>C) and HIWI3 rs11703684 (C>T) polymorphisms and mutational analysis of TDRD5 gene in idiopathic non-obstructive azoospermia in a case-control study including 226 non-obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 35 publications
(32 reference statements)
0
17
0
Order By: Relevance
“…Normally, these elements are kept under strict control by epigenetic factors, but during epigenetic reprogramming, they become reactivated. Sperm piRNA is needed for sustaining genomic integrity during these events, and a dysfunctional piRNA machinery may result in idiopathic nonobstructive azoospermia and infertility [42]. It has been recognized, however, that in the paternal germline, there are two separate populations of piRNAs, upregulated at two different time‐points.…”
Section: Introductionmentioning
confidence: 99%
“…Normally, these elements are kept under strict control by epigenetic factors, but during epigenetic reprogramming, they become reactivated. Sperm piRNA is needed for sustaining genomic integrity during these events, and a dysfunctional piRNA machinery may result in idiopathic nonobstructive azoospermia and infertility [42]. It has been recognized, however, that in the paternal germline, there are two separate populations of piRNAs, upregulated at two different time‐points.…”
Section: Introductionmentioning
confidence: 99%
“…Non-obstructive azoospermia (NOA) is the most severe form of azoospermia and lacking of effective cures, whereas patients with obstructive azoospermia usually can be treated with assisted reproductive technologies (ART) surgery and bypass infertility in this way. To date, mutations on several genes have been identified causative for, or associated with NOA, the acknowledged genes include X chromosome linked genes TEX11, 47 FAM47C, 8 MAGEB4, 9 and AR; 10,11 and autosomal genes PIWIL1, 1215 BRCA2, 16 BOLL and DAZL, 17,18 TEX15, 1921 SYCP3, 22 NR5A1, 23 SOHLH1, 24 WT1, 25,26 TAF4B and ZMYND15, 27 FANCM, 28 SPINK2, 29 TEX14, 30 DNAH6, 30 MEIOB, 31 RNF212 and STAG3, 32 XRCC2, 33,34 TDRD7, 35 TDRD9, 36 DMC1, 37 SYCE1, 38 NPAS2, 39,40 MCM8, 41 MEI1, 42,43 and STX2 44 . A surprisingly large proportion of total genes are specifically expressed in the male testis, 45 suggesting that thousands of genes may involve in the spermatogenic process.…”
Section: Introductionmentioning
confidence: 99%
“…One study looked at the connection between SNPs of several key proteins involved in piRNA signaling pathway and idiopathic non-obstructive azoospermia (NOA) using a sample collection of Iranian infertile males with NOA. It turns out that rs508485 polymorphism in HIWI is correlated with the increased risk if azoospermia in the studied population [86]. If the research above showed an indirect relationship between piRNA and NOA, another recent research demonstrated the relationship more directly.…”
Section: Pirnas In Other Types Of Diseasesmentioning
confidence: 81%